CEPHALIC CHAETOTAXY OF THE LAST INSTAR LARVA OF A PYRALID : CORCYRA CEPHALONICA (STAINTON) (LEPIDOPTERA) - ROSE, H. S.; BEHL, N. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Twenty one setae and eleven punctures have been observed on various areas of the head capsule of C. cephalonica (Staint.).